DETERMINATION OF MINERAL COMPOSITION OF ORGANIC AND CONVENTIONAL BEVERAGES BY DISPERSIVE ENERGY X-RAY FLUORESCENCE SPECTROMETRY - CONSOLI, L.; CAMARGO, G. A. (Revista Brasileira de Engenharia de Biossistemas, 2012)
Fruits are natural sources of minerals whose ingestion is recommended in a balanced diet. The increasing consumption of fruit-based beverages demands the development of rapid methods to evaluate their quality parameters. X-ray fluorescence spectrometry is an analytical-nuclear technique that is gaining space in the environmental and geological fields, and has been explored modestly in the food field. The main objective of this work was to develop a methodology to determine the mineral content of fruit-based beverages by applying this technique. Beverages manufactured from organic and conventional fruit varieties were evaluated, aiming to compare their nutritional value. The research was divided into three steps: in the first step, a direct measurement of the samples was made, that is, without prior preparation; in the second, standard curves were prepared with the elements of calcium and potassium, based on the category of ’fine samples’. Lastly, these curves were used to determine concentrations of calcium and potassium in the samples of juices and pulps prepared as ’fine samples’. The fine sample measurements showed results more exact compared to that obtained from the direct measurements. From the data evaluated, it was not possible to attribute better nutritional quality to either the organic or conventional samples.